Best Factors Influencing Students' Interest in Learning Mathematics in Junior High School in The Digital Era - satria mulyajaya; Serina Anggraini (Mathematics Research and Education Journal, 2022)
This study aims to describe or examine the best factors influencing students' interest in learning mathematics in junior high school. This research is quantitative research with a correlation approach. The population of this study was all high school students in Riau Province. The sample is part of the selected students with a cluster random sampling approach. The instrument used is a questionnaire designed and validated in terms of content and constructs. The research variables used were parental support, study friends, learning environment, and interest in learning. Data analysis using path analysis. The analysis results show that the three variables affect students' interest in learning in the Digital Era with a significantly smaller value of 0.05